The Implementation of Gender Mainstreaming Policy in Indonesian Local Government – The Case of Salatiga City 2017-2022 - Takayasa, Tika Ifrida (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) UIN Walisongo, 2023)
Gender mainstreaming is a strategy for integrating gender issues into urban development. Gender mainstreaming was implemented in accordance with Presidential Instruction No. 6 of 2000 but was not incorporated into local regulations until 20 years later. Salatiga City is leading the way in gender mainstreaming in urban development, implementing it according to the Mayor's Regulation No. 5 of 2021. The development of Salatiga City from 2017-2022 has achieved remarkable results at the national level, as reflected in the Human Development Index (HDI) and the Gender Development Index (GDI). This research goes beyond the numbers to see how local gender policies are responsive by looking at the factors of participation, benefits, control, and access for all parties. This research uses the theory of PUG implementation by looking at the seven prerequisites for gender mainstreaming in regional development: commitment, policies, institutions, resources, analytical tools, disaggregated data, and community participation. The results of the study show that the implementation of gender mainstreaming in Salatiga City has improved each year and that all the PUG requirements have been met. However, the drivers and implementers of mainstreaming at government level have not fully understood the PPRG in its implementation. Women are still lagging in three crucial areas of society: education, health and the economy.The implementation of gender mainstreaming necessitates the collaboration of all stakeholders, including the government, civil society, and the private sector. To achieve equitable and sustainable development, it is essential that these entities work in concert